Calculator-Based Emulator to Enhance Statistics Teaching: A University Case Study - Flores-Ccanto, Florencio; Chirinos-Maldonado, Daniel-Marcos; Menacho-Vargas, Isabel; Galvez-Morales, Lourdes; Lau-Mego, Cesar-Salvador; Flores-Lira, Jhoseline-Gianella; Villegas-Lira, Marianela-Marilú (Journal of Posthumanism, 2025)
Statistical competence is fundamental in various fields, but many students and researchers have difficulties in effectively applying statistical concepts. This study aims to evaluate and measure the impact of the integration of the CASIO fx-570 emulator calculator in the teaching of statistics at the university level with a sample of 170 university students, which was divided into two groups (control and experimental) and was where the CASIO fx-570 emulator was used in order to integrate theory with practice and foster a more intuitive and engaging learning experience. Pre- and post-tests assessed the effect of the intervention on conceptual, procedural and attitudinal learning dimensions. Mann-Whitney U tests revealed statistically significant improvements (p < 0.05) in all dimensions for the experimental group. These results demonstrate the potential of the CASIO fx-570 emulator to improve the learning of statistics in university students. In conclusion, it is necessary to take into account current educational needs and take advantage of technological advances to bridge the gap between statistical theory and practice, as well as to foster a more intuitive understanding of statistics in research.